2020
DOI: 10.22159/ijap.2020.v12s3.39472
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Nestin in the Induced Differentiation Into Neurons of Rat Bone Marrow Mesenchymal Stem Cells by Neurotrophin-3 (Nt-3)

Abstract: Objective: The aim of this study was to examine the role of NT-3 as a single neurotrophic factor in the expression of nestin in the neural differentiation of MSCs. Methods: MSCs were isolated from rat bone marrow and induced with NT-3 at concentrations of 20, 25, and 30 ng/ml for 7 and 14 d (the control was no NT-3). Nestin underwent immunocytochemical analysis on days 7 and 14. Five high-power random fields were documented. Results: A post-hoc analysis using LSD after one-way ANOVA test yielded a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…The administration of neurotrophins is a potential approach to the therapy of neurodegenerative disorders or injuries such as Parkinson's disease (PD), Alzheimer's disease (AZ), spinal cord, brain trauma, and brain tumors [31]. reported that MSCs can be differentiated into neurons with a medium containing NT-3 as a single neurotrophic factor and expressed nestin in the immature neural differentiation of MSCs [20]. Thus, in this study, NT-3 was used to investigate the expression of MAP-2 in the mature neural differentiation of MSCs with a single neurotrophic factor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The administration of neurotrophins is a potential approach to the therapy of neurodegenerative disorders or injuries such as Parkinson's disease (PD), Alzheimer's disease (AZ), spinal cord, brain trauma, and brain tumors [31]. reported that MSCs can be differentiated into neurons with a medium containing NT-3 as a single neurotrophic factor and expressed nestin in the immature neural differentiation of MSCs [20]. Thus, in this study, NT-3 was used to investigate the expression of MAP-2 in the mature neural differentiation of MSCs with a single neurotrophic factor.…”
Section: Discussionmentioning
confidence: 99%
“…showed that the addition of bFGF, EGF, and BDNF to the medium induced the differentiation of rat bone marrow MSCs into neurons and glia and characterized neural markers like A2B5, beta-III-tubulin, PSA-NCAM, and MAP-2) [19]. also reported that NT-3 role as a single neurotrophic factor in the expression of nestin in the immature neural differentiation of MSCs [20]. A combination of growth factors and neurotrophic factors consistently demonstrated efficacy in neural differentiation protocols.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The cells were passaged at 70% to 80% confluency [20]. The stem cells were previously confirmed by Ghorbanian et al (2012) [21,22].…”
Section: Rbmscs Isolation and Culturementioning
confidence: 94%
“…Keterangan: Kontrol negatif (A), Kontrol positif (B), SPM dalam medium yang ditambah NT-3 hari ke-7 (C), dan hari ke-14 (D). warna coklat menunjukkan sel positif Nestin (perbesaran 400x) 20 dari sumsum tulang tikus dapat berdiferensiasi menjadi neuron dengan penambahan NT-3 dalam medium kultur. Perkembangan neuron diamati dengan ekspresi penanda Nestin pada hari ke-7 dan ke-14 (Gambar 4).…”
Section: Gambar 4 Ekspresi Nestin Pada Diferensiasi Spmunclassified